STRATEGI PEMASARAN DALAM MENINGKATKAN KEPUASAN KONSUMEN DI ALFAMART GUNUNG SARI, BALIKPAPAN - Savira, Dellis; Amaliyah, Amaliyah (Bussman Journal : Indonesian Journal of Business and Management, 2024)
Businesses are trying to improve their marketing techniques to maximize client happiness. Along with the rapid development of the current retail business, if the company wants to increase its growth and development, competent management is needed. The marketing mix and marketing strategy are the two most important parts of any marketing plan. The purpose of the research is to find out the marketing strategy on alfamart in increasing customer satisfaction. The research method uses qualitative. Interviews were conducted with management and several consumers. The results of this study show that the marketing strategy carried out by Alfamart is a bundling strategy for several products offered as a promo to increase the selling value of products in maximizing sales for products that are not familiar in the market. The strategy carried out in combining several goods/products that are used as sales packages into one price to be offered to consumers with an economical selling value than the product price. Alfamart's marketing strategy which includes the 4Ps is that the products provided by alfamart are also in accordance with what consumers need, have sendri products that have an "A" logo and are guaranteed quality. The price is very affordable and when you have ALfamartku the price becomes cheaper because of discounts on certain days such. The place given is very strategic, to find out the location of the nearest Alfamart you can download Alfagift. Promotion/Promotion: Alfamart usually promotes through Leaflets, which are distributed to the public, Instagram Ads, Youtube Ads, Posters, Alfamart official website ads and JSM (Friday, Saturday, Sunday)